Risk factors for recurrence after endoscopic papillectomy in ampullary adenomas: a retrospective case–control study - Kun Liu; Yuhang Zhuang; Ningjing Gao; Muhan Ni; Xiang Zhang; Peng Yan; Quan Zhou; Zhao Shi; Pin Wang; Dehua Tang; Ying Lv; Lei Wang; et al. (Therapeutic Advances in Gastroenterology)
Background: Endoscopic papillectomy (EP) has emerged as a preferred treatment modality for ampullary adenomas, offering a less-invasive alternative to surgical resection. However, concerns persist regarding the potential for incomplete resection and subsequent recurrence. Objectives: This study aims to evaluate the efficacy of EP in treating ampullary adenomas and to identify risk factors associated with recurrence. Design: This study was a single-center, retrospective case–control study. Methods: We retrospectively analyzed patients who underwent EP at Nanjing Drum Tower Hospital between January 2010 and December 2022. Recurrence rates were assessed, and potential risk factors for recurrence were analyzed using univariate and multivariate Cox proportional hazards models. Hazard ratios (HR) with corresponding 95% confidence intervals (CI) were calculated. Results: Among the 137 patients who achieved complete resection, 21 (15.3%) experienced recurrence. The median follow-up period was 17.7 months (interquartile range (IQR) 11.7–37.5), and the median time-to-recurrence was 16.2 months (IQR 9.9–33.9). Of the 21 recurrence cases, 11 (52.3%) were managed successfully with repeat endoscopic intervention, while 6 (28.6%) required pancreatoduodenectomy. Significant risk factors for recurrence included familial adenomatous polyposis (FAP; HR = 9.3; 95% CI: 2.8–30.4; p  < 0.001), pancreaticobiliary (PB) subtype (HR = 3.2; 95% CI: 1.5–11.3; p  = 0.006), and high-grade dysplasia (HGD; HR = 2.6; 95% CI: 1.1–6.2; p  = 0.036). Comprehensive sensitivity and subgroup analyses consistently confirmed the stability of these risk factors. Conclusion: EP is an effective treatment for ampullary adenomas; however, recurrence remains a significant concern, particularly among patients with FAP, PB subtype, and HGD.